Android complex information flow analysis method based on communicating sequential process - Zhanhui YUAN; Zhi YANG; Hongqi ZHANG; Shuyuan JIN; Xuehui DU (网络与信息安全学报)
Android privacy leak problem is becoming more and more serious.Information flow analysis is a main method to find privacy leak.Traditional information flow analysis methods mainly focus on single accessibility analysis, which is difficult to analyze complex information flow.An information flow analysis method based on communication sequence process was proposed.The formal model of application behavior was established, which can fully describe the information flow of program.The process trace equivalence analysis method could automatically verify complex information flow problems such as information flow association and information flow constraints.This method could detect whether the application program leaks sensitive information.Experimental results show that the accuracy of the proposed method can reach 90.99%.